Hand-grip strength as an indicator for predicting the success in martial arts athletes - Iermakov, S. S.; Podrigalo, L. V.; Jagiello, W. (Archives of Budo, 2016)
Background and Study Aim: One main scientific practical tasks in sports is increasing an efficiency and forecasting the sportsmanship growth. The purpose of this work is answer the question whether based on the hand grip strength of different martial arts` athletes it is possible of their successfulness prognostication.